Nitrogen Requirements of Sweet Corn Grown on Mea Rim Soil Series - Kaweewong, Jakchaiwat; Moonta, Adirek (Thai Journal of Science and Technology, 2024)
Sweet corn (Zea mays L. saccharata) is one of the most important crops in Thailand. Nitrogen fertilizer is the major input in sweet corn production. Proper nitrogen fertilizer management practices can increase productivity and reduce production costs sustainably. This study aims to investigate the effect of nitrogen on growth, yield component, and yield of sweet corn grown on Mea Rim soil series. The experiment was laid out in the randomized complete block design (RCBD) with three replications. The nitrogen fertilizer treatment comprised control, 0, 5, 10, 20, 30 and 40 kg N/rai as urea (46-0-0). Sweet corn was harvested at 95 days. The results of the nitrogen fertilizer application showed that growth, yield, and yield components of sweet corn were significantly different. The application rate of nitrogen fertilizer in the range of 20-30 kg N/rai gave the maximum average of plant height (262.45 cm) aboveground dry weight (1,031.8 kg/rai), diameter of the husked and unhusked ear (5.39 and 4.92 cm, respectively) length of unhusked and husked ears (23.20 and 17.23 cm, respectively), and kernel number per ear (427.3 kernels). The nitrogen fertilizer rate at 30 kg N/rai gave the maximum average grain yield at 1,792 kg/rai. Besides, yield response to nitrogen fertilizer rate of sweet corn grown on Mea Rim soil serieswas 1,682.1 kg/rai when applying nitrogen fertilizer rate at 29.84 kg N/rai. Based on the results of the experiment, using nitrogen fertilizer ranged from 25-30 kg N/rai is recommended for growing sweet corn in Mea Rim soil series with low nitrogen content.